1994
DOI: 10.1109/68.265887
|View full text |Cite
|
Sign up to set email alerts
|

All optical wavelength conversion by SOA's in a Mach-Zehnder configuration

Abstract: Absb'nct-Penalty free wavelength conversion is demonstrated at 2.5 GbiVs over a wavelength span of 12 nm by the use of SOA's in a Mach-Zehnder configuration. An increase in the extinction ratio is measured for the converted signal compared to the input signal implying signal regeneration as well as wavelength conversion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
2

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 182 publications
(51 citation statements)
references
References 5 publications
0
49
0
2
Order By: Relevance
“…3. In these gates, the optical input signal controls the phase difference between the interferometer arms through the relation between the carrier density and the refractive index in the SOAs (cross-phase modulation, XPM); thereby a CW light or a pulse train can be gated [29] or control pulses can be used to gate the input signal.…”
Section: Xpm Gatesmentioning
confidence: 99%
“…3. In these gates, the optical input signal controls the phase difference between the interferometer arms through the relation between the carrier density and the refractive index in the SOAs (cross-phase modulation, XPM); thereby a CW light or a pulse train can be gated [29] or control pulses can be used to gate the input signal.…”
Section: Xpm Gatesmentioning
confidence: 99%
“…The speed of the wavelength conversion can also be enhanced by using two cascaded SOAs, called 'Turbo-Switch' (Manning et al, 2006). Wavelength conversion can also be achieved by arranging two or more SOAs in the MZI configuration (Ratovelomanana et al, 1995, Durhuus et al, 1994, Idler et al, 1995, as shown in Fig. 8.…”
Section: Wwwintechopencommentioning
confidence: 99%
“…Several schemes were developed during the decade of the 1990s (Durhuus et al 1994), and many others have been proposed since then ( (Stubkjaer, 2000;Wolfson et al 2000;Leuthold, J. 2001;Nakamura et al 2001;M.…”
Section: Wavelength Convertersmentioning
confidence: 99%